2022
DOI: 10.4490/algae.2022.37.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in seaweed seedling production: a review of eucheumatoids and other valuable seaweeds

Abstract: Modern seaweed farming relies heavily on seedlings from natural beds or vegetative cuttings from previous harvests. However, this farming method has some disadvantages, such as physiological variation in the seed stock and decreased genetic variability, which reduces the growth rate, carrageenan yield, and gel strength of the seaweeds. A new method of seedling production that is sustainable, scalable, and produces a large number of high-quality plantlets is needed to support the seaweed farming industry. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…Seaweed-derived science parks have gained global recognition owing to their versatile applications across multiple industries. The commercial significance of each SP depends on its specific composition and bioactivity, which can vary with seaweed conditions, harvesting season, and environmental factors (Nagahawatta et al 2021, Jiksing et al 2022. in host cells (Wei et al 2022).…”
Section: Potentials For Commercial and Indus-trial Applicationmentioning
confidence: 99%
“…Seaweed-derived science parks have gained global recognition owing to their versatile applications across multiple industries. The commercial significance of each SP depends on its specific composition and bioactivity, which can vary with seaweed conditions, harvesting season, and environmental factors (Nagahawatta et al 2021, Jiksing et al 2022. in host cells (Wei et al 2022).…”
Section: Potentials For Commercial and Indus-trial Applicationmentioning
confidence: 99%
“…Plant growth regulators (PGRs), are organic compounds that are synthetic (or naturally derived from microorganisms) and have growth and developmental regulatory effects similar to those of natural plant hormones (Rademacher, 2015). Plant hormones such as auxin, gibberellin, and cytokinin can be exogenously applied as PGRs to regulate the growth and reproduction of plants and seaweeds (Duran-Medina et al, 2017;Miyakawa and Tanokura, 2017;Song et al, 2020;Hernandez-Garcia et al, 2021;Nedved et al, 2021;Jiksing et al, 2022). Chen et al (2022) reported that exogenous application of auxin can promote biomass production and branching in Gracilariopsis lemaneiformis.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing, however, that extensive use of vegetative propagation methods can lead to vigor loss, reduced production capacity, and increased susceptibility to pathogens. Thus, these methods must be combined with reproductive cell (spores or gametes)-based techniques to improve economic cultivars like C. chamissoi [ 28 ].…”
Section: Introductionmentioning
confidence: 99%